ANALYSIS OF THE ABILITY OF PRIMARY TEACHER EDUCATION STUDENTS TO DEVELOP THEMATIC LEARNING MATERIALS IN 2013 CURRICULUM - Siti Halidjah (Universitas Tanjungpura, 2020)
The content of the Pre-service Primary Teacher Education Study Program of FKIP Untan has provided students with mastery of scientific substance in preparing thematic learning teaching materials for 2013 Curriculum. The study aimed to describe the ability of Primary teacher Education students to prepare thematic learning teaching materials for 2013 curriculum. The research was a qualitative descriptive study. The subjects of this study were students of the PPL Regular Program class 2017. The data source in this study was the teaching material documents constructed by students. The research procedure used the stages of planning, implementing, analyzing data, and writing reports. Data collection techniques used document study techniques with data collection tools in the form of teaching material documents. The research data analysis was carried out by following the data analysis flow developed by Miles and Hubberman (1992: 15-20). The analysis activity begins with data collection, data reduction, data presentation, and conclusion/verification. The ability of students to construct 2013 thematic learning teaching materials was very good. It can be seen from the percentage of results achieved, namely 87.50% (7 students) obtained scores in the range 81-100 and only 12.50 (1 student) scored in the range 61-80. For every aspect assessed, the average student ability was also good. It can be seen from the percentage achieved, namely 58.33% (7 aspects) obtained scores in the range 81-100 and 41.67 (5 aspects) obtained scores in the range 61-80.